STUDIES ON THE INFLUENCE OF THE LEVEL OF FINANCIAL SUPPORT ON THE TREND OF AREA CULTIVATED IN ORGANIC FARMING SYSTEM - Veronica LUNGU; Daniel Valeriu ULIU; Marius VLADU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Organic farming promotes extensive agricultural practices, providing environmental public goods and responding to society's demand for the use of environmentally friendly agricultural practices, but also to increased consumer demand for organic products. Organic agriculture contributes to mitigating the greenhouse effect and global warming, through the ability to sequester carbon in the soil. Many practices used in organic agriculture (for example, incorporation of plant residues into the soil, use of green crops and crop rotation, the ability of vegetables and legumes to fix nitrogen in the soil), increase the return of carbon to the soil, increase productivity and promote carbon storage. Organic agriculture is a dynamic sector in Romania that has seen an upward evolution in recent years. Through the study carried out, we aimed to highlight the evolution of agriculture in an ecological system with the help of compensatory payments granted by the European Union, in the South - West Oltenia Region of Romania, in the period 2019 - 2021. It was found that the surface of 18,420 hectares in 2019 increased to 36,241 hectares in 2021, and until 2024 it is expected that the trend of the area cultivated in the ecological system also to grow.